2021
DOI: 10.1371/journal.pone.0247545
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and survival response of Atta cephalotes (Hymenoptera: Myrmicinae) workers to Metarhizium anisopliae infection: Potential role of their associated microbiota

Abstract: Leaf-cutting ants of the genera Atta and Acromyrmex are at constant risk of epizootics due to their dense living conditions and frequent social interactions between genetically related individuals. To help mitigate the risk of epizootics, these ants display individual and collective immune responses, including associations with symbiotic bacteria that can enhance their resistance to pathogenic infections. For example, Acromyrmex spp. harbor actinobacteria that control infection by Escovopsis in their fungal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…The same Pseudonocardiaceae (Actinobacteria: Actinomycetales) OTUs were found across all four ant species, despite the lack of actinobacterial biofilm on Atta cuticles. Interestingly, recent evidence suggests that cuticular microbiota in Atta do not play a defensive role, at least against the Metarhizium anisopliae fungal entomopathogen (53). While multiple Actinobacterial strains can occur on fungus-growing ant worker cuticles, we found that only one or two strains dominated the bacterial communities of queen and gyne mesosomas, similar to what has been previously shown on cuticles of callow workers of Acromyrmex leafcutter ants (28).…”
Section: Discussionmentioning
confidence: 99%
“…The same Pseudonocardiaceae (Actinobacteria: Actinomycetales) OTUs were found across all four ant species, despite the lack of actinobacterial biofilm on Atta cuticles. Interestingly, recent evidence suggests that cuticular microbiota in Atta do not play a defensive role, at least against the Metarhizium anisopliae fungal entomopathogen (53). While multiple Actinobacterial strains can occur on fungus-growing ant worker cuticles, we found that only one or two strains dominated the bacterial communities of queen and gyne mesosomas, similar to what has been previously shown on cuticles of callow workers of Acromyrmex leafcutter ants (28).…”
Section: Discussionmentioning
confidence: 99%
“…A formiga-cortadeira A. sexdens rubropilosa representa um dos insetos mais importantes sob o ponto de vista econômico, pois além de apresentar ampla ocorrência no Brasil, está entre os herbívoros mais vorazes e de maior variedade alimentar SIMÕES, 2014;VASCONCELOS et al, 2006).…”
Section: Formigas-cortadeirasunclassified